The influence of depression-PTSD comorbidity on health-related quality of life in treatment-seeking veterans. Issue 1 (31st December 2020) - Forchuk, Callista; Nazarov, Anthony; Hunt, Renee; Davis, Brent; St. Cyr, Kate; Richardson, J. Don
ABSTRACT: Objective: Posttraumatic stress disorder (PTSD) and depression substantially impair health-related quality of life (HRQOL) for many Canadian Armed Forces (CAF) veterans. Although PTSD and depression are highly comorbid, little is known about whether the disorders may interact in their association with HRQOL. We sought to investigate whether depressive symptoms modify the relation between PTSD and HRQOL in treatment-seeking veterans. Method: We accessed the clinical data of 545 CAF veterans aged 18 to 65 years who were seeking treatment at a specialized clinic in London, Ontario. We used hierarchical linear regression to assess the additive and multiplicative relations between depression and PTSD symptoms on HRQOL, controlling for age and alcohol/substance abuse. Simple slopes were examined to probe significant interactions. Results: Probable PTSD and major depression were present in 77.4% and 85.3% of the sample, respectively, and 73.0% of the sample presented with probable PTSD-depression comorbidity. Depression symptoms significantly modified the relation between PTSD symptoms and overall mental HRQOL (β = 0.12, p <0.001, ∆ R 2 = 0.014), and role impairment due to emotional difficulties (β = 0.20, p <0.001, ∆ R 2 = 0.035). Simple slope analyses revealed the impact of PTSD was greater among those with lower depression symptoms and became weaker with greater depression symptom severity. In adjusted models, only depression was significantly associated with all mental and physical HRQOL domains; PTSD was not associated with physical HRQOL, role emotional impairment, or vitality. Conclusions: For those with severe comorbid depression, PTSD symptoms were no longer associated with mental HRQOL, particularly in areas related to emotional functioning. Findings suggest the importance of targeting depression in patients presenting with PTSD-depression comorbidity.